2010
DOI: 10.3109/17453674.2010.524595
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the material properties of the normal supraspinatus tendon by nicotine treatment in a rat model

Abstract: Background and purposeSeveral studies have shown that nicotine has a detrimental effect on the development of rotator cuff tear. However, little is known about its mechanism. We evaluated the effect of nicotine on the maximum tensile load, the maximum tensile stress, and the elastic modulus of the supraspinatus tendon in a rat model.Methods27 rats were randomly assigned to 3 groups. Subcutaneously implanted osmotic pumps delivered two different concentrations of nicotine solution (high dose: 45 ng/mL; low dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
2
26
1
2
Order By: Relevance
“…In previous studies, a decrease in the elastic modulus of the gastrocnemius tendon was detected during stretching exercises. Thus, a decrease in tendon injuries along with stretching exercises has been assumed to correlate with a decrease in the elastic modulus of the tendon 10 , 27 . In addition, supraspinatus tendon tears that initiate at the anterior third of the tendon, where the elastic modulus is higher than at the posterior and middle thirds, have been reported 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, a decrease in the elastic modulus of the gastrocnemius tendon was detected during stretching exercises. Thus, a decrease in tendon injuries along with stretching exercises has been assumed to correlate with a decrease in the elastic modulus of the tendon 10 , 27 . In addition, supraspinatus tendon tears that initiate at the anterior third of the tendon, where the elastic modulus is higher than at the posterior and middle thirds, have been reported 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The elastic modulus of the supraspinatus was found to be higher in high‐ and low‐level nicotine exposure groups in comparison to the control group. Accordingly, Ichinose et al 10 postulated that the increase in the elastic modulus as a result of nicotine might predispose the individual to an increase in tendon injuries. However, they also reported that the nicotine dosage applied to the animals was considerably higher in comparison to the exposure levels of smoking individuals and that their findings should be confirmed with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has also demonstrated alterations in biomechanical properties of the supraspinatus tendon in the setting of nicotine, producing increased elastic modulus of the supraspinatus tendon in a rat model, an indicator for increased stiffness which is more predisposed to injury. 97 Nicotine has been reported to elevate collagen synthesis and increased collagen cross-linking in animal models. These processes may lead to increased tissue fibrosis and subsequent higher elastic modulus.…”
Section: Smokingmentioning
confidence: 99%
“…Além disso, o estudo de Ichinose et al 20 em 2010 revelou que existe uma redução na produção de oxido nítrico e aumento na síntese de colágeno em ratos expostos a fumaça, fatores que podem contribuir para lesões de tendões musculares devido ao aumento da sua elasticidade 20 . Por este motivo, se faz necessária a mensuração da FMP nesta população, para guiar os profissionais de saúde quanto as suas práticas clinicas.…”
Section: Em 2002 Tanamakiunclassified